Method for removing aluminum and copper from iron phosphorus slag and application
Through a one-step process, combined with ball mill screening, activation and dispersion and acid leaching reaction, the problems of complex removal of aluminum and copper in iron phosphorus slag in the prior art, large reagent consumption and environmental impact were successfully solved, and the efficient removal of aluminum and copper in the iron phosphorus slag in the prior art was achieved. The low loss of iron and phosphorus provides an environmentally friendly and efficient resource recycling solution.
Patent Information
- Application Number
- CN202411569030.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-05
- Publication Date
- 2025-02-07
AI Technical Summary
When removing aluminum and copper from iron and phosphorus slag, the process is complicated, the reagents are consumed heavily, and there is a potential threat to the environment and human health. It is difficult to effectively remove aluminum and copper in one-step method, while reducing the loss of iron and phosphorus. .
The one-step process is adopted, through a combination of ball mill screening, activation dispersion and acid leaching reaction, and the activation dispersion and acid leaching reaction are combined with surfactant and gentle organic acid to carry out activation dispersion and acid leaching reaction, and aluminum and copper in the iron and phosphorus slag are preferred.
It has achieved simplification of the process, improved environmental protection of reagents, efficient removal of aluminum and copper, and low loss of iron and phosphorus, providing a high-quality and high-value iron and phosphorus resource recycling solution.
Smart Images

Figure FT_1 
Figure FT_2
Abstract
Description
Technical Field
[0001] The invention relates to the field of recycling waste lithium iron phosphate batteries, and in particular to a method for removing aluminum and copper from iron-phosphorus slag and application thereof. Background Art
[0002] In recent years, the new energy vehicle industry has experienced rapid development. This trend has not only led to a significant increase in the sales of new energy vehicles, but also greatly increased the demand for power batteries. As battery capacity decays and performance declines, they face retirement. It is predicted that by 2030, about 6 million electric vehicle battery packs will be retired each year, of which lithium iron phosphate (LiFePO4) will account for 2.5% of the total. 4 ) batteries account for a considerable proportion. The recycling of lithium iron phosphate batteries is of great significance.
[0003] At present, the recycling technology of waste lithium iron phosphate batteries mainly includes hydrometallurgical technology, pyrometallurgical technology and repair and regeneration technology. Hydrometallurgical technology has become the mainstream technology due to its mature process, energy saving and high efficiency, and significant economic benefits. In order to improve the recovery rate of lithium, hydrometallurgical technology currently generally adopts a process route of prioritizing lithium extraction, that is, first extracting lithium from lithium iron phosphate, and then recycling the iron-phosphorus residue to prepare regenerated iron phosphate or lithium iron phosphate.
[0004] Since the iron-phosphorus slag contains aluminum and copper as impurities of the current collector, the purity of the regenerated iron-phosphorus product is affected and must be removed first. Invention CN 117500753 A Iron Phosphorus discloses a method for removing aluminum and copper from iron-phosphorus slag. The method first acid-leaches the iron-phosphorus slag to obtain a fully acid-soluble solution, and then removes copper in two steps. The first step is to add iron to the acid leaching solution to replace copper, and the second step is to add sulfides such as sodium sulfide to further remove copper. Aluminum is then removed from the solution by extraction to obtain a purified iron-phosphorus solution. Invention CN 118019707 A discloses a method for removing aluminum from lithium iron phosphate waste by directional circulation, wherein lithium iron phosphate waste, iron salt solution and reducing agent are mixed, and a mixed salt solution containing aluminum ions and ferrous ions and lithium iron phosphate material after aluminum removal are obtained by the first reaction; the pH of the mixed salt solution is adjusted, and after the second reaction, solid-liquid separation is performed to obtain aluminum hydroxide slag and a solution containing ferrous iron; finally, the obtained ferrous iron solution is mixed with an oxidant, the pH is adjusted, and an iron salt solution is obtained by the third reaction. The processes described in the above schemes are all for removing copper and aluminum in steps or removing aluminum alone. The processes are relatively complicated, the reagent consumption is large, and the use of certain reagents such as sulfides has adverse effects on the environment and human health. Therefore, it is urgent to develop an effective, convenient and environmentally friendly method for removing aluminum and copper from iron-phosphorus slag. If copper and aluminum can be removed in one step and the loss of iron and phosphorus can be reduced as much as possible, it will have great technical advantages. Summary of the invention
[0005] In order to solve the above technical problems, the present invention provides a method for removing aluminum and copper from iron-phosphorus slag and its application.
[0006] In a first aspect, the present invention provides a method for removing aluminum and copper from iron-phosphorus slag, comprising the following steps: 1) Ball milling and screening: ball mill and screen the iron-phosphorus slag raw materials; 2) Activation dispersion: Mix the raw materials after ball milling and screening with the activation dispersion agent and perform activation dispersion; 3) Removal of aluminum and copper: mixing an acid leaching agent with the activated and dispersed material and performing an acid leaching reaction and solid-liquid separation to obtain low-aluminum-copper iron-phosphorus slag; wherein the activated and dispersed agent contains a surfactant, and the acid leaching agent contains an organic acid and an oxidant.
[0007] The present invention adopts a one-step method to preferentially remove aluminum and copper from iron-phosphorus slag, which can effectively obtain low-aluminum-copper iron-phosphorus slag, and can better recover subsequent iron and phosphorus. The method of the present invention has the characteristics of simple process, green and environmentally friendly reagents, better impurity removal efficiency and comprehensive effect of iron and phosphorus loss, and lays a foundation for high-quality and high-value utilization of iron and phosphorus resources in waste lithium iron phosphate battery materials.
[0008] Preferably, in step 1), the iron-phosphorus slag raw material is iron-phosphorus slag (lithium extraction residue) obtained after lithium extraction from waste lithium iron phosphate batteries.
[0009] The method provided by the present invention is to preferentially remove aluminum and copper from the iron-phosphorus slag produced after lithium extraction from waste lithium iron phosphate batteries. The iron-phosphorus slag has high chemical stability. The surfactant used to activate and disperse the iron-phosphorus slag and the mild organic acid used for acid leaching can effectively remove aluminum and copper while significantly reducing the loss rate of iron and phosphorus. The method provided by the present invention to obtain low-aluminum and copper purified iron-phosphorus slag from lithium extraction residues of waste lithium iron phosphate battery materials also has the characteristics of high impurity removal efficiency, simple process flow, green environmental protection, etc., and better provides high-quality and high-value utilization of iron and phosphorus resources in waste lithium iron phosphate batteries.
[0010] Further preferably, in step 1), a grading screen is used for screening, and the screening specification is 150-250 mesh, preferably 200 mesh; and / or, the ball milling time is 20-40 min, the rotation speed is 50-70 r / min, and the ball-to-material ratio is 8-12:1. The present invention optimizes the process, and the obtained refined particles can increase the contact area between the particles and the solution, improve the reaction efficiency, and facilitate subsequent treatment processes, such as filtration, and improve the efficiency of the entire process.
[0011] Preferably, in step 2), the activation dispersing agent is selected from one or more of sodium dodecylbenzenesulfonate solution (SDBS), sodium dodecyl sulfate solution (SDS), and cetyltrimethylammonium bromide solution (CTAB), preferably sodium dodecylbenzenesulfonate solution (SDBS); preferably sodium dodecylbenzenesulfonate solution; preferably, the concentration of the activation dispersing agent is 0.001-0.005 mol / L. .
[0012] According to the present invention, the activation and dispersing agent adopts a specific surfactant aqueous solution, and its concentration is preferably 0.001-0.005 mol / L, which is conducive to better activation and dispersion and subsequent treatment effect.
[0013] Further preferably, in step 2), the liquid-solid ratio of the activated dispersing agent to the raw material after ball milling and screening is 20-80:1 mL / g; and / or, the activation dispersion time is 0.5-1 h, and the temperature is 30-90 ° C. The subsequent removal effect of the present invention can be further improved by optimizing the activation dispersion conditions.
[0014] Preferably, in step 3), the acid leaching reagent contains an oxidant with a mass fraction of 30±5%, and the oxidant is hydrogen peroxide (H 2 O 2 ).
[0015] Preferably, the organic acid can be an organic acid solution commonly used in the art, preferably selected from formic acid (HCOOH), acetic acid (C 2 H 4 O 2 ) and citric acid (C 6 H 8 O 7 ) one or more; the oxidant is hydrogen peroxide; Further preferably, in step 3), the concentration of the organic acid solution used in the acid leaching reagent is 2.5-3 mol / L; the volume fraction of the oxidant in the mixed liquid is 4 vol%-12 vol%. The mixed liquid is a mixture of the acid leaching reagent and the material to be treated. In the present invention, the oxidant and the organic acid are added to the activated and dispersed material, and the obtained mixed liquid is acid-leached, especially the use of a certain concentration and amount of hydrogen peroxide can better cooperate with other reagents, improve the removal effect and ensure the quality of subsequent products.
[0016] In the present invention, by improving the method of preferentially removing aluminum and copper from the iron-phosphorus slag produced after lithium extraction from waste lithium iron phosphate batteries, the dried lithium extraction residue is subjected to ball milling treatment, and is screened using a grading screen, the grading screen specification is preferably 200 meshes, and then the raw materials after the ball milling and screening are activated and dispersed using a reagent, and the activated powder reagent is preferably a sodium dodecylbenzene sulfonate solution. Then, an organic acid and an oxidant solution are added to the activated and dispersed material for acid leaching, the organic acid is preferably formic acid, and the oxidant is preferably a certain amount of hydrogen peroxide, and the purified iron-phosphorus slag is filtered to have a better aluminum and copper removal effect while further reducing the loss rate of iron and phosphorus.
[0017] More preferably, in step 3), the reaction temperature is 60-90° C. and the reaction time is 1-3 h.
[0018] In the present invention, by optimizing the treatment methods, treatment reagents and conditions in each treatment step, the aluminum and copper removal effect can be greatly improved, while the loss of iron and phosphorus can be reduced and the impurity removal efficiency can be improved.
[0019] According to a preferred embodiment of the present invention, a method for preferentially removing aluminum and copper from iron-phosphorus slag produced after lithium extraction from waste lithium iron phosphate batteries comprises the following specific steps: 1) Ball milling and screening: Grind the dried lithium extraction residue and use a sieve to screen it. The ball milling time is 30 minutes, the speed is 60r / min, the ball-to-material ratio is 10:1, and the sieve specification is 200 mesh.
[0020] 2) Activation and dispersion: The raw materials after ball milling and screening are activated and dispersed using an activation powder reagent; the activation powder reagent is a sodium dodecylbenzene sulfonate solution (SDBS), the SDBS concentration is 0.001~0.005mol / L, the reaction time is 0.5~1h, and the reaction temperature is 30~90℃.
[0021] 3) Organic acid to remove aluminum and copper: Add organic acid solution to the activated and dispersed material for acid leaching, preferably adding HCOOH and H 2 O 2 Solution, HCOOH concentration is 2.5~3mol / L, H 2 O 2 The dosage is 4vol%~12vol%, the leaching liquid-solid ratio is 20~60:1mL / g, the reaction temperature is 60~90℃, the leaching time is 1~3h, and low-aluminum-copper iron-phosphorus slag is obtained after filtration.
[0022] In a second aspect, the present invention provides low-aluminum-copper ferrophosphorus slag obtained by the above-mentioned method of removing aluminum and copper from ferrophosphorus slag.
[0023] In a third aspect, the present invention provides the above-mentioned method for removing aluminum and copper from iron-phosphorus slag or the use of the low-aluminum-copper iron-phosphorus slag obtained by the above-mentioned method for removing aluminum and copper from iron-phosphorus slag in the recovery of waste lithium iron phosphate batteries, preferably in the recovery of waste lithium iron phosphate batteries to prepare regenerated iron phosphate or lithium iron phosphate.
[0024] The beneficial effects of the present invention are at least that: the present invention firstly uses a surfactant to activate and disperse the iron-phosphorus slag, and at the same time uses a mild organic acid for acid leaching, which can effectively inhibit the loss of iron and phosphorus, and preferentially remove aluminum and copper in one step. The present invention provides a method for extracting lithium residues from waste lithium iron phosphate battery materials to obtain low-aluminum and copper purified iron-phosphorus slag, which has the characteristics of simple process flow, green environmental protection, good comprehensive recovery effect, etc., and lays a foundation for the high-quality and high-value utilization of iron-phosphorus resources. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] In order to more clearly illustrate the technical solutions in the present invention or the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0026] Figure 1 (a) and (b) are the SEM image of the iron-phosphorus slag before impurity removal in Example 1.
[0027] Figure 2 (a) and (b) are the SEM image of the iron-phosphorus slag before impurity removal in Example 2. DETAILED DESCRIPTION
[0028] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. The following embodiments are used to illustrate the present invention but are not used to limit the scope of the present invention.
[0029] If no specific technology or conditions are specified in the examples, the technology or conditions described in the literature in the field or the product instructions are used. The implementation conditions in the examples can be further adjusted according to specific experimental conditions or factory conditions. If no implementation conditions are specified, they are usually the conditions in routine experiments. The materials, reagents, etc. used in the following examples can be obtained from commercial sources unless otherwise specified.
[0030] The following examples are used to illustrate the present invention but are not intended to limit the scope of the present invention.
[0031] The iron phosphorus slag used in the present invention has a Fe content of ≥27%, a P content of ≥15%, an Al content of ≥0.3%, and a Cu content of ≥0.01%. In the following examples, the Fe content of the iron phosphorus slag raw material used is 29.44%, the P content is 17.92%, the Al content is 0.66%, and the Cu content is 0.03%.
[0032] Example 1
[0033] This embodiment provides a method for preferentially removing aluminum and copper from iron-phosphorus slag produced after lithium extraction from waste lithium iron phosphate batteries. The specific steps are as follows.
[0034] (1) Load the iron-phosphorus slag into the ball mill at a ball-to-material ratio of 10:1, set the speed to 600 r / min, and ball mill for 30 min. After the milling, collect the powder and pass it through a 200-mesh grading sieve. Take the fine particles under the sieve for later use.
[0035] (2) Weigh 0.0696g of sodium dodecylbenzene sulfonate (SDBS) and add it to 40mL of water. Stir magnetically to ensure that it is fully dissolved to prepare a 0.005mol / L SDBS aqueous solution. Weigh 1g of 200-mesh iron-phosphorus slag and add it to the SDBS aqueous solution at a liquid-solid ratio of 40:1mL / g. React at 90℃ for 1h to complete the dispersion and activation of the iron-phosphorus slag.
[0036] (3) Add 4.53 mL of 99 wt% formic acid to the material solution obtained in step (2) to make the formic acid concentration in the solution 3 mol / L, add 3.2 mL of 30 wt% hydrogen peroxide to make the volume fraction of hydrogen peroxide in the mixed liquid 8 vol%, and the liquid-solid ratio is 40:1 mL / g. After reacting in a water bath environment at a temperature of 90°C for 3 hours, filter, and dry the filter residue for 12 hours to obtain the iron-phosphorus slag after removing copper and aluminum. The removal rates of aluminum and copper are 43.35% and 82.00%, respectively, and the loss rates of iron and phosphorus are 3.45% and 5.32%, respectively.
[0037] Example 2
[0038] The present invention provides a method for preferentially removing aluminum and copper from iron-phosphorus slag produced after lithium extraction from waste lithium iron phosphate batteries, and the specific steps are as follows.
[0039] (1) Load the iron-phosphorus slag into the ball mill at a ball-to-material ratio of 10:1, set the speed to 600 r / min, and ball mill for 30 min. After the milling, collect the powder and pass it through a 200-mesh grading sieve. Take the fine particles under the sieve for later use.
[0040] (2) Weigh 0.0522g of sodium dodecylbenzene sulfonate (SDBS) and add it to 30mL of water. Stir magnetically to ensure that it is fully dissolved to prepare an SDBS aqueous solution. Weigh 1g of 200-mesh iron-phosphorus slag and add it to the SDBS aqueous solution at a liquid-solid ratio of 30:1mL / g. React at 90℃ for 1h to complete the dispersion and activation of the iron-phosphorus slag.
[0041] (3) Add 3.40 mL of 99 wt% formic acid to the solution obtained in step (2) to make the formic acid concentration in the solution 3 mol / L, then add 2.4 mL of 30 wt% hydrogen peroxide to make the volume fraction of hydrogen peroxide in the solution 8 vol%, and the liquid-solid ratio is 30:1 mL / g. After reacting in a water bath environment at a temperature of 90°C for 3 hours, filter, and dry the filter residue for 12 hours to obtain the iron-phosphorus slag after the removal of copper and aluminum. The removal rates of aluminum and copper are 33.55% and 65.00%, respectively, and the loss rates of iron and phosphorus are 3.27% and 5.04%, respectively. Figure 1-Figure 2 They are the SEM images and EDS images of Examples 1 and 2, respectively. The material particles in the images have a certain uniformity, and it can be seen from the EDS images that the aluminum and copper content in the treated materials is greatly reduced.
[0042] Example 3
[0043] The present invention provides a method for preferentially removing aluminum and copper from iron-phosphorus slag produced after lithium extraction from waste lithium iron phosphate batteries, and the specific steps are as follows.
[0044] (1) Load the iron-phosphorus slag into the ball mill at a ball-to-material ratio of 10:1, set the speed to 600 r / min, and ball mill for 30 min. After the milling, collect the powder and pass it through a 200-mesh grading sieve. Take the fine particles under the sieve for later use.
[0045] (2) Weigh 0.0522g of sodium dodecylbenzene sulfonate (SDBS) and add it to 30mL of water. Stir magnetically to ensure that it is fully dissolved to prepare an SDBS aqueous solution. Weigh 1g of 200-mesh iron-phosphorus slag and add it to the SDBS aqueous solution at a liquid-solid ratio of 30:1mL / g. React at 90℃ for 1h to complete the dispersion and activation of the iron-phosphorus slag.
[0046] (3) Add 2.83 mL of 99 wt% formic acid to the solution obtained in step (2) to make the formic acid concentration in the solution 2.5 mol / L, add 1.8 mL of 30 wt% hydrogen peroxide to make the volume fraction of hydrogen peroxide in the solution 6 vol%, and the liquid-solid ratio is 30:1 mL / g. After reacting in a water bath environment at a temperature of 90°C for 3 hours, filter, and dry the filter residue for 12 hours to obtain the iron-phosphorus slag after the removal of copper and aluminum. The removal rates of aluminum and copper are 25.73% and 52.78%, respectively, and the loss rates of iron and phosphorus are 3.00% and 4.29%, respectively.
[0047] Example 4
[0048] This embodiment provides a method for preferentially removing aluminum and copper from iron-phosphorus slag produced after lithium extraction from waste lithium iron phosphate batteries. The specific steps are as follows.
[0049] (1) Load the iron-phosphorus slag into the ball mill at a ball-to-material ratio of 10:1, set the speed to 600 r / min, and ball mill for 30 min. After the milling, collect the powder and pass it through a 200-mesh grading sieve. Take the fine particles under the sieve for later use.
[0050] (2) Weigh 0.0522g of sodium dodecylbenzene sulfonate (SDBS) and add it to 30mL of water. Stir magnetically to ensure that it is fully dissolved to prepare an SDBS aqueous solution. Weigh 1g of 200-mesh iron-phosphorus slag and add it to the SDBS aqueous solution at a liquid-solid ratio of 30:1mL / g. React at 80℃ for 0.5h to complete the dispersion and activation of the iron-phosphorus slag.
[0051] (3) Add 2.83 mL of 99 wt% formic acid to the material solution obtained in step (2) to make the formic acid concentration in the solution 2.5 mol / L, and add 1.8 mL of 30 wt% hydrogen peroxide to make the volume fraction of hydrogen peroxide in the solution 6 vol%, and the liquid-solid ratio 30:1 mL / g. After reacting in a water bath environment at a temperature of 60°C for 3 hours, filter, and dry the filter residue for 12 hours to obtain the iron-phosphorus slag after removing copper and aluminum. The removal rates of aluminum and copper are 19.25% and 45.63%, respectively, and the loss rates of iron and phosphorus are 1.56% and 2.83%, respectively.
[0052] Example 5
[0053] The embodiment provides a method for preferentially removing aluminum and copper from iron-phosphorus slag produced after lithium extraction from waste lithium iron phosphate batteries, and the specific steps are as follows.
[0054] (1) Load the iron-phosphorus slag into the ball mill at a ball-to-material ratio of 10:1, set the speed to 600 r / min, and ball mill for 30 min. After the milling, collect the powder and pass it through a 200-mesh grading sieve. Take the fine particles under the sieve for later use.
[0055] (2) Weigh 0.0261g of sodium dodecylbenzene sulfonate (SDBS) and add it to 30mL of water. Stir magnetically to ensure that it is fully dissolved to prepare an SDBS aqueous solution. Weigh 1g of 200-mesh iron-phosphorus slag and add it to the SDBS aqueous solution at a liquid-solid ratio of 30:1mL / g. React at 60℃ for 0.5h to complete the dispersion and activation of the iron-phosphorus slag.
[0056] (3) Add 2.67 mL of 99 wt% formic acid to the material solution obtained in step (2) to make the formic acid concentration in the solution 2.5 mol / L, add 1.8 mL of 30 wt% hydrogen peroxide to make the volume fraction of hydrogen peroxide in the solution 6 vol%, and the liquid-solid ratio 30:1 mL / g, react in a water bath environment at a temperature of 60°C for 3 hours, filter, and dry the filter residue for 12 hours to obtain the iron-phosphorus slag after the removal of copper and aluminum. The removal rates of aluminum and copper are 13.19% and 32.63% respectively, and the loss rates of iron and phosphorus are 0.98% and 1.28% respectively.
[0057] Comparative Example 1
[0058] (1) Load the iron-phosphorus slag into the ball mill at a ball-to-material ratio of 10:1, set the speed to 600 r / min, and ball mill for 30 min. After the milling, collect the powder and pass it through a 200-mesh grading sieve. Take the fine particles under the sieve for later use.
[0059] (2) Weigh 0.0576 g of citric acid and add it to 30 mL of water. Stir magnetically to ensure that it is fully dissolved to prepare a 0.1 mol / L citric acid aqueous solution.
[0060] (3) Weigh 1g of 200-mesh iron-phosphorus slag and add it to a citric acid aqueous solution with a liquid-to-solid ratio of 30:1mL / g. Add 1.8mL of 30wt% hydrogen peroxide to make the volume fraction of hydrogen peroxide in the solution 6vol%. React in a water bath at 60℃ for 1h and then filter. The removal rates of aluminum and copper are 4.93% and 7.27% respectively, and the loss rates of iron and phosphorus are 5.65% and 5.00% respectively.
[0061] Comparative Example 2
[0062] (1) Load the iron-phosphorus slag into the ball mill at a ball-to-material ratio of 10:1, set the speed to 600 r / min, and ball mill for 30 min. After the milling, collect the powder and pass it through a 200-mesh grading sieve. Take the fine particles under the sieve for later use.
[0063] (2) Weigh 0.34 mL of 70 wt% methanesulfonic acid solution, add it to 30 mL of water, and stir magnetically to ensure that it is fully dissolved to prepare a 0.1 mol / L methanesulfonic acid aqueous solution.
[0064] (3) Weigh 1 g of 200-mesh iron-phosphorus slag and add it to a methanesulfonic acid aqueous solution. Add 1.8 mL of 30 wt% hydrogen peroxide to make the volume fraction of hydrogen peroxide in the solution 6 vol% and the liquid-solid ratio 30:1 mL / g. React in a water bath at 60 °C for 1 h and then filter. The removal rates of aluminum and copper were 14.99% and 14.60%, respectively, and the loss rates of iron and phosphorus were 17.11% and 14.00%, respectively.
[0065] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for removing aluminum and copper from iron-phosphorus slag, characterized in that: The following steps are involved: 1) Ball milling and screening: ball mill and screen the iron-phosphorus slag raw materials; 2) Activation dispersion: Mix the raw materials after ball milling and screening with the activation dispersion agent and perform activation dispersion; 3) Removal of aluminum and copper: mixing an acid leaching agent with the activated and dispersed material and performing an acid leaching reaction and solid-liquid separation to obtain low-aluminum-copper iron-phosphorus slag; wherein the activated and dispersed agent contains a surfactant, and the acid leaching agent contains an organic acid and an oxidant.
2. The method for removing aluminum and copper from iron-phosphorus slag according to claim 1, characterized in that: In step 1), the iron-phosphorus slag raw material is the iron-phosphorus slag after lithium is extracted from waste lithium iron phosphate batteries.
3. The method for removing aluminum and copper from iron-phosphorus slag according to claim 1 or 2, characterized in that: In step 1), screening is performed using a graded sieve with a screening specification of 150-250 mesh; and / or, the ball milling time is 20-40 min, the rotation speed is 50-70 r / min, and the ball-to-material ratio is 8-12:
1.
4. The method for removing aluminum and copper from iron-phosphorus slag according to any one of claims 1 to 3, characterized in that: In step 2), the activation dispersing agent is selected from one or more of sodium dodecylbenzenesulfonate solution, sodium dodecyl sulfate solution, and hexadecyltrimethylammonium bromide solution, preferably sodium dodecylbenzenesulfonate solution; preferably, the concentration of the activation dispersing agent is 0.001-0.005 mol / L.
5. The method for removing aluminum and copper from iron-phosphorus slag according to claim 4, characterized in that: In step 2), the liquid-to-solid ratio of the activated dispersing agent to the raw material after ball milling and screening is 20-80:1 mL / g; and / or, the activation dispersion time is 0.5-1 h, and the temperature is 30-90 °C.
6. The method for removing aluminum and copper from iron-phosphorus slag according to any one of claims 1 to 5, characterized in that: In step 3), the acid leaching reagent contains an oxidant with a mass fraction of 30±5%, and the oxidant is hydrogen peroxide.
7. The method for removing aluminum and copper from iron-phosphorus slag according to claim 6, characterized in that: In step 3), the concentration of the organic acid solution used in the acid leaching reagent is 2.5-3 mol / L; the volume fraction of the oxidant in the mixed liquid is 4 vol%-12 vol%.
8. The method for removing aluminum and copper from iron-phosphorus slag according to any one of claims 1 to 7, characterized in that: In step 3), the reaction temperature is 60-90°C and the reaction time is 1-3h.
9. The low-aluminum-copper ferrophosphorus slag obtained by the method for removing aluminum and copper from ferrophosphorus slag according to any one of claims 1 to 8.
10. Use of the low-aluminum-copper iron-phosphorus slag obtained by the method for removing aluminum and copper from iron-phosphorus slag according to any one of claims 1 to 8 or the method for removing aluminum and copper from iron-phosphorus slag according to claim 9 in the recovery of waste lithium iron phosphate batteries, preferably in the recovery of waste lithium iron phosphate batteries to prepare regenerated iron phosphate or lithium iron phosphate.
Citation Information
Patent Citations
Method for removing aluminum and copper in ferrophosphorus slag and application of method
CN117500753A
Method for removing aluminum from lithium iron phosphate waste through directional circulation
CN118019707A
Cited By
Recycling method of lithium iron phosphate pole piece waste
CN120646798A